2018
DOI: 10.3389/fphar.2018.00370
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Proteomics and Bioinformatics Approach Reveals the Anti-inflammatory Mechanism of Carnosic Acid

Abstract: Drastic macrophages activation triggered by exogenous infection or endogenous stresses is thought to be implicated in the pathogenesis of various inflammatory diseases. Carnosic acid (CA), a natural phenolic diterpene extracted from Salvia officinalis plant, has been reported to possess anti-inflammatory activity. However, its role in macrophages activation as well as potential molecular mechanism is largely unexplored. In the current study, we sought to elucidate the anti-inflammatory property of CA using an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…Antitumor[176]d. Anti-inflammatory[177]e. Inhibitory effect of digestive enzymes (lipase, α-amylase, and α-glucosidase)[178]f.…”
Section: Introductionmentioning
confidence: 99%
“…Antitumor[176]d. Anti-inflammatory[177]e. Inhibitory effect of digestive enzymes (lipase, α-amylase, and α-glucosidase)[178]f.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the proteomics technology has become an important support for the rapid development of modern biotechnology. Proteomics essentially refers to studying the characteristics of proteins on a large scale and understanding key pathways through information network analysis [31]. In this work, a comprehensive approach combining proteomics and pharmacological experimental studies is used to research the anti-in ammatory effects of PHI and mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we reported that isosibiricin exerts a significant anti-neuroinflammatory effect on LPS-treated BV-2 cells. LPS is a common inflammation inducer that is used to investigate different types of inflammatory pathology, such as tissue inflammation [ 23 ], vascular inflammation [ 34 ] and myocarditis [ 35 ]. Dopaminergic neurons play an important role in the pathological process of Parkinson’s disease [ 36 ], and LPS is widely used to induce neuroinflammation to establish models of Parkinson’s disease.…”
Section: Discussionmentioning
confidence: 99%
“…A single cycle was carried out at 95 °C for 30 s, 58 °C for 30 s and 63 °C for 30 s, and this cycle was repeated 40 times. The relative transcriptional levels of DRD1 and DRD2 normalized to those of GAPDH was calculated by the comparative 2 −ΔΔCT method [ 23 ].…”
Section: Methodsmentioning
confidence: 99%